Investigating the Efficacy of Various Natural Products in Raw Form against Multidrug-Resistant Bacteria - Alanazi, Hamad H.; Aldughmani, Hussain Ali G.; Mazhari, Bi Bi Zianab (Infectious Disorders - Drug Targets, 2025)
BackgroundThe alarming increase in antibiotic resistance urges alternative and efficacious antimicrobial solutions. Historically, medicinal plants have been used for therapeutic purposes, such as relieving pain and healing wounds. The evaluation of the natural therapeutic effects of medicinal plants in a manner that resembles how humans typically consume them is lacking. In this study, many medicinal plants known to have some antimicrobial effects, including Frankincense, Garlic, Myrrh, and Ginger, were evaluated for their direct antibacterial activity in raw form.Materials and MethodsThe direct antimicrobial activity of medicinal plants was evaluated against a variety of Gram-positive and Gram-negative bacterial strains, such as Staphylococcus aureus (S. aureus.), Acinetobacter baumannii and Klebsiella pneumoniae using agar well diffusion method and turbidity measurements in suspension culture.ResultsOut of all the tested medicinal plants, only raw garlic (Allium sativum) powder, when dissolved in water or vinegar, offered a straightforward antibacterial activity. A combination of garlic extract and vinegar increased antibacterial activity. Aqueous garlic extracts displayed robust antimicrobial activity against many resistant bacteria. Other medicinal plants used in this study had absent or minimal antibacterial effects.ConclusionOnly garlic in its raw form was effective against antibiotic-resistant bacteria. The increase in the antibacterial activity of garlic when combined with vinegar suggests synergistic activity of garlic. The straightforward antibacterial action of raw garlic may be strategically harnessed to combat the continuous challenge of increasing antibiotic resistance. This work promotes additional testing of more natural products (in raw form) and assesses their therapeutic effects clinically.
Keywords: natural products